Mikrozonasi Indeks Kerentanan Seismik Menggunakan Metode HVSR di Kapanewon Galur, Kabupaten Kulon Progo - Mardiyanto; Kalyana Mita, Ailing; Sunardi, Bambang (Stasiun Geofisika Kelas I Sleman, 2023)
Kapanewon Galur in Kulon Progo is close to the Progo Fault, a fault with signs of activity about 35 km long. This area is included in a seismically active area because it is close to plate subduction activity, making it prone to earthquakes. This condition makes Kapanewon Galur an area that has the potential to experience earthquakes. The longer existence of the Progo Fault compared to the Opak Fault indicates a greater risk, allowing larger and more destructive earthquakes to occur in the future, compared to the 2006 earthquake in Bantul. Obtaining the dominant frequency (f0) and amplification factor (A0) values using the HVSR method helps to see the seismic vulnerability index (Kg) in the area. The microzonation of the area is also an important criterion for identifying earthquake-prone areas in the Kapanewon Galur area. Findings from research in Kapanewon Galur using the HVSR method show that the f0 ranges from 0.15 to 1.57 Hz, A0 value ranges from 1.24 to 3.61, and Kg ranges from 4.8 to 87.85. By considering these values, it can be concluded that Kapanewon Galur can be classified as an area with a high seismic vulnerability index.